Stakeholders throughout an infrastructure megaproject : Case Olkiluoto 3 - Peltoluhta, Juha (My University, 2025)
The growing global economy and the rising demand for clean energy calls for huge investment into energy infrastructure. This investment is increasingly often carried out in the form of large-scale, complex ventures: megaprojects. Megaprojects face many challenges, due to which they are often going over time and over budget. One of the megaproject characteristics that cause these challenges is their complex stakeholder field. Megaprojects are multi-actor processes, with multiple parties from different backgrounds involved in planning and construction throughout the project. This thesis explores how a megaproject progresses, what stakeholders are involved in each part of the project, and how the stakeholders are positioned at each step of the project. To answer these questions, previous megaproject literature is examined. In forming the theoretical framework, it is then combined with stakeholder theory, and the theory of stakeholder salience. The study is carried out in the form of an intensive case study on the nuclear reactor construction project Olkiluoto 3. The project timeline is divided based on the findings of internal events of the project. These three different timeframes are then studied separately and compared. The findings reveal that the stakeholder landscape is highly dynamic, with new stakeholders emerging and the salience of existing ones changing throughout the different phases of the project. The megaproject progress and challenges are aligned with previous literature. External stakeholders such as governing bodies emerge as the most frequently coded. The dynamic stakeholder landscape and the interesting changes in salience show that there is need for megaproject management to not only identify the stakeholders but keep surveilling their salience that may change drastically, potentially resulting in challenges.
Keywords: megaprojects, nuclear, Olkiluoto 3, salience, stakeholders